Anterior cruciate ligament and popliteus tendon injuries associated with a cyamella: a rare case report - Chodavarapu, Mounika N. S.; Kambhampati, Srinivas B. S.; Chinta, Shyam K.; Bhogadi, Harsha (International Journal of Research in Orthopaedics, 2025)
The cyamella is a rare sesamoid bone in the popliteus muscle. This small ossicle may alter the biomechanics of the popliteus, potentially affecting knee function leading to instability. We report a 19-year-old male with a right knee injury from an auto rollover accident. Imaging revealed an anterior cruciate ligament (ACL) rupture, an intra-articular loose body, a cyamella, and a popliteal tendon avulsion. ACL reconstruction was performed, and the cyamella and loose body were excised. The tendon avulsion was repaired with a suture anchor. At one-year follow-up, the patient had full knee movement without instability. This case highlights a rare injury combination and excellent surgical outcomes when promptly identified and treated.